The Influence of Competence and Leadership on Employee Performance with Commitment as an Intervening Variable - Isra Misra; Ali Sadikin; Sardimi; Ajahari Ajahari; Aditya Ahmad (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
Employee performance is a key factor in determining an organization's success. In several studies, the factors influencing employee performance are competence and leadership. Meanwhile, an equally important factor in strengthening the above variables is employee commitment. This study aims to investigate whether competence and leadership have a significant positive impact on employee performance, with commitment serving as an intervening variable. This research is quantitative. The sample in this study consisted of 52 respondents, who were selected using the snowball sampling technique. The data source was a questionnaire distributed randomly using Google Forms. The data analysis technique utilized the Smart-PLS 4.0 application, which comprises inferential statistical tests, model measurement, model design, hypothesis testing, and model evaluation. The results of the study show (1) directly, competence has a significant positive effect on employee performance with a p-value of 0.013<0.05, but does not affect commitment because the p-value is 0.336>0.05, (2) leadership has a direct significant positive effect on employee commitment and performance with a p-value of 0.001<0.05, (3) commitment has a direct significant positive effect on employee performance 0.001<0.05. Indirectly, commitment is unable to strengthen the competence variable in relation to employee performance, as indicated by a p-value of 0.361, which is greater than 0.05. At the same time, leadership can strengthen the leadership variable on employee performance with a p-value of 0.04<0.05. This study contributes to the development of management science, particularly in understanding the factors that influence employee performance. While the limitation of this study is that the sample is too small, future researchers can conduct further research by increasing the sample size. Research approaches can also be used with a variety of more varied approaches